Community Empowerment in Developing Village Potentials in Ecotourism Activities in Abiansemal Badung Bali - I Wayan Wesna Astara; I Nyoman Putu Budiartha; I Wayan Rideng; Made Bagoes Wiranegara Wesna; Made Setiasa (Law Doctoral Community Service Journal, 2023)
American writer wrote a book, dubbing the island of Bali "The Last Paradise". Bali does not have natural resources, but when the Dutch ruled Bali, this culture was exploited for profit. During the era of independence and the New Order's development, it was planned to develop Bali as a tourism destination. Then Nusa Dua developed as mass tourism, and Kuta from ecotourism developed into mass tourism so that tourism capitalism drives the tourism business sector in Kuta. North Badung is now being developed into an ecotourism and/or tourism village. North Badung, especially Abiansemal Village, is a village in the Abiansemal District, Badung Regency, Bali Province. Abiansemal Village is one of the villages in the Abiansemal sub-district, which is located 1.5 Kilometers from the District Capital, and 10 Kilometers from the Regency City. At present the Abiansemal Village is led by Mr. Perbekel Ida Bagus Bhisma Wiratma S.H. The boundaries of the Abiansemal Village area are to the north by the Setra/Kembengan Cemetery, to the south by the Tukad / Campuhan Gerih River, to the west by the Tukad / Bangiang River, and to the east by the Tukad / Ayung River.